Celiakie--závazné onemocnĕní - Prokopová, L (Vnitrni lekarstvi, 2003)
Celiac disease (Celiacal sprue = gluten-sensitive enteropathy = netropic sprue) is the all-life genetically determined autoimmune disease with permanent intolerance to gluten, which damages the intestinal mucous membrane and alterates the immune system. The atrophy and typical inflammatory changes of mucous membrane results in malabsorption with diarrhea, general weakness, anemia and weight loss. The clinical picture of celiac disease is considerably heterologous. Only 20-30% of patients suffer from active-classical form of the disease. Non-diagnosed, inactive forms of the disease form 70-80% of cases of celiac disease in adult individuals. The therapy is based on diet without gluten. Application of the diet usually results in clinical improvement and signs of the disease are diminished. The relapse of celiac disease occurs after a gluten load. Celiac disease and dermatitis Duhring are considered to be two equal forms how gluten enteropathy becomes manifest. Celiac disease is often associated with other autoimmune diseases (e.g. insulin-dependent diabetes mellitus, autoimmune thyreoiditis). Untreated celiac disease still represents a serious medical risk, since it is an important precancerosis. Introduction of highly sensitive methods for the determination of antibodies against endomysium and tissue transglutaminase significantly extended possibilities of diagnosis and screening for celiac disease. It became obvious that the real incidence of celiac disease including the non-diagnosed forms of the disease in the European population is greater than 1:200 to 1:250.
Keywords: celiakie; Humans; lidé; Celiac Disease